The emerging role of corporate governance on environmental sustainability - Mukesh Kumar Mishra (SSRN, 2023)
Sustainability is indeed one of the most significant challenges facing the world today, driven by a multitude of interconnected issues, including climate change, social inequality, and environmental degradation. In response to these challenges, various stakeholders, including policymakers, regulators, and intergovernmental organizations, are taking substantial actions to address and mitigate these concerns. This highlights the need for more comprehensive and immediate action at various levels, including the private sector. Changing attitudes and expectations about the role of business in society are driving a shift towards a more responsible and sustainable approach to corporate conduct. Companies can respond to social issues in ways that are good for both business and society. Companies will need reliable data as well as sustainability expertise for the Corporate Sustainability Reporting Process. This paper contribute the embracing a holistic approach to corporate social responsibility (CSR) and integrating ESG principles into their core strategies, companies can not only contribute to addressing pressing global challenges but also enhance their reputation, attract socially conscious consumers and investors, and ultimately secure long-term success in an evolving business landscape where sustainability and social responsibility are paramount.
Keywords: Q50; Q51; G30; Q01; 330; Environment; Corporate Governance; Sustainability; Public Policy